2018
DOI: 10.1002/rmb2.12214
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in oncofertility care worldwide and in Japan

Abstract: BackgroundOncofertility is a crucial facet of cancer supportive care. The publication of guidelines for the cryopreservation of oocytes and ovarian tissue is becoming increasingly prevalent in Japan and an updated overview is necessary.MethodsIn order to provide an updated overview of oncofertility care, original research and review articles were searched from the PubMed database and compared in order to present clinical care in Japan.ResultsIn Western countries, various methods for ovarian stimulation, such a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…In our case report, fertility preservation of the patient's oocytes or ovaries was not performed before cancer therapy. Cryopreservation of sperm, embryos, unfertilized mature oocytes and ovarian tissues is performed for fertility preservation before AYA patients with cancer irreversibly lose fertility due to cancer therapy . Guidelines from the American Society of Clinical Oncology state that the possibility of cancer treatment‐induced infertility should be discussed with all cancer patients of reproductive age before adjuvant chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our case report, fertility preservation of the patient's oocytes or ovaries was not performed before cancer therapy. Cryopreservation of sperm, embryos, unfertilized mature oocytes and ovarian tissues is performed for fertility preservation before AYA patients with cancer irreversibly lose fertility due to cancer therapy . Guidelines from the American Society of Clinical Oncology state that the possibility of cancer treatment‐induced infertility should be discussed with all cancer patients of reproductive age before adjuvant chemotherapy .…”
Section: Discussionmentioning
confidence: 99%
“…Thus, all healthcare providers should pay attention to fertility preservation guidelines to make it possible for AYA patients to conceive in the future before they are treated with chemotherapy, radiation therapy, or surgery . In order to provide information related to onco‐fertility counseling, as of December 2017, a regional onco‐fertility network was established in Gifu, Shiga, Saitama and 18 other prefectures in Japan . This network makes it easier for oncologists and reproduction specialists to exchange information about fertility preservation and cancer treatment in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, however, transportation of HFF may be beneficial for oncofertility applications in cases where the hospital performing the pathological diagnosis of resected ovaries is geographically distant from the hospital involved in FP. Such hospitals are relatively rare in Japan; for instance, while in 2017 there were more than 400 cancer hospitals nationwide, there were only 30 hospitals with the ability to cryopreserve both oocytes and ovarian tissue . It may also allow human oocytes to be stored as research materials during transportation from operating hospitals to research institutions.…”
Section: Discussionmentioning
confidence: 99%
“…hospitals with the ability to cryopreserve both oocytes and ovarian tissue. 37 It may also allow human oocytes to be stored as research materials during transportation from operating hospitals to research institutions. In this study, mature oocytes in meiosis II were obtained in both the transportation and non-transportation groups, and we anticipate that it will be feasible to use these oocytes for the study of blastocysts, for instances using parthenogenetic activation techniques.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that the pregnancy rate per cryopreserved embryo is 30–35%, and the risk of congenital anomaly is not increased [ 66 , 67 , 68 , 69 ]. One retrospective study demonstrated that pregnancy rate per transfer for cancer patients was similar to patients who underwent IVF due to tubal factor infertility (37% versus 43%, p = 0.49) and live birth rate per transfer was also was not significantly different (30% versus 32%, p = 0.85) [ 70 ].…”
Section: Fertility Preservation Optionsmentioning
confidence: 99%